Strengthening the Pancasila Student Profile Through a Social Approach: A Study on the Implementation of the Independent Curriculum in Elementary Schools - Nora Sara Damayanti; Imaduddin, Muhammad; Sari, Dyta Agnes Layung (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The Pancasila Student Profile is a program aimed at strengthening character education and encouraging students to provide solutions to problems in their surrounding environment. This study aims to describe the implementation of the Independent Curriculum at SDN Antirogo 04, focusing on learning strategies, student involvement in the Pancasila Student Profile Strengthening Project (P5), and the challenges encountered. This research employs a qualitative descriptive method. Data were collected through observation, interviews, and questionnaires. The findings show that the Independent Curriculum is implemented through project-based learning that promotes interdisciplinary integration, character development, and the utilization of local resources as a form of integrating local wisdom into the learning process. Teachers act as facilitators who support active and contextual learning, in line with differentiated and student-centered learning principles. The Independent Curriculum, which incorporates elements of local wisdom, has proven effective in creating a democratic, creative, and meaningful learning environment, while also strengthening the holistic and sustainable development of student character within the framework of the Pancasila Student Profile.